Hydrodynamic condition and suspended sediment diffusion in the Yellow Sea and East China Sea. Issue 8 (20th August 2016) - Li, Guangxue; Qiao, Lulu; Dong, Ping; Ma, Yanyan; Xu, Jishang; Liu, Shidong; Liu, Yong; Li, Jianchao; Li, Pin; Ding, Dong; Wang, Nan; Olusegun A, Dada; et al.
Abstract: Based on monthly averaged current, temperature, and salinity, we analyzed the changes of suspended sediment concentration (SSC) and the relationship with the warm current, coastal current, and cold water mass (CWM) in the East China Seas (ECSs). The result shows that the coastal current and surface diluted water are the route for transporting suspended sediment. The Kuroshio and its derived warm current branches play the important role of the continental shelf circulation system and control the diffusion of suspended sediment. High SSC has been mainly concentrated in coastal current and CWM. Two sedimentary dynamic patterns have been identified. The winter‐half‐year pattern lasts almost 7 months. The coastal currents off the Shandong Peninsula, northern Jiangsu, Zhejiang‐Fujian coast are the main routes for diffusion and deposition of the suspended sediment from the Yellow River and Changjiang River. The summer‐half‐year pattern is characterized by the well‐developed CWM. All CWMs have a unique function to trap suspended sediment under the thermocline due to weakening tidal current and residual current there. These CWMs in the Yellow Sea (YS) and north ECS are connected together. The layer above the thermocline is characterized by diluted water with low salinity, high temperature. Suspended sediment can be transported into the Okinawa Trough and the South Korea coast during this period. A strong eddy always occur nearby the Kuroshio bend at northeast Taiwan, which has promoted the exchange between the ECS shelf and Okinawa Trough, and the development of the shelf edge current and Taiwan warm current (TWC). Key Points: Two dynamic sedimentary patterns driven by Asian monsoon and Kuroshio have been identified in ECSs Suspended sediment diffused by coastal current most come from Changjiang and Yellow River in ECSs Suspended sediments are trapped in the CWM and coastal current route